As ressignificações da representação e da legitimidade política: um estudo sobre representantes no CEDCA-MG - Eduardo Moreira da Silva (2013)
The thesis deals with the concepts of political representation and legitimacy focusing on Brazilian institutional experience created after enactment of the 1988s Constitution. Since then, the management councils have spread across the country at all three levels of government. In recent years a research agenda was established with international repercussions, on the called Participatory Institutions (IPs). Despite the extensive academic literature on these IPs, few studies were dedicated to the experiences of the state level of government. In order to fill part of this gap, we investigated the Conselho Estadual dos Direitos da Criança e do Adolescente (CEDCA-MG). The representative functions performed by civic actors also gained evidence and space on research agenda in recent years, which has been termed as a pluralization of forms of representation. This discussion outlines specific features that differentiate the way it has developed in the international arena in relation to the Brazilian context. The main reason for it is there is a wide range of institutions in which seats are provided for the government and society to discuss the planning, monitoring and control of public policies. In this scenario, in which we observe the possible absence of an authorization process (elections or draw) that initiates the representative activity, we investigate what are the possible grounds of the authority of the councilors of the CEDCA-MG? These basis can be generalized to other councils? The methodology of the history of concepts guided the construction of the theoretical chapters of the thesis, the first dedicated to the concept of political representation and the second to legitimacy. From the critical dialogue with this literature, we formulated the hypothesis that the legitimacy of the councilors derive from multiple sources: authorization, publicity, accountability and recognition. Based on these four elements, we seek to evaluate the representative actions performed by the members of the council. The thesis was constructed based on a case study method (N = 1), in which we used the following techniques: document analysis, the application of a questionnaire, semi-structured interviews and participant observation. The data allow us to identify the four elements in some practices adopted by the board and its members. However, practices framed in questions of publicity and accountability are characterized as occasional actions, isolated and not as established procedures routinely performed by them. In this sense, if analyzed from the whole set of the elements proposed, the legitimacy of CEDCAs counselors is questionable. The data also show the performance of an informal actor with strong influence in the council, the Front for the Defense of the Rights of the Child and Adolescent (FDDCA-MG). Some of its members attend the CEDCAs meetings and have the ability to put issues on the agenda. Moreover, they influence the selection process of civil societys members and the choice of boards chairman, when this function is not being occupied by a governments member. We conclude, therefore, that despite the questioning of the legitimacy of the representative function of civil societys counselors, the historical involvement of FDDCA in defense of the rights of children and adolescents, its huge capillarity in the State and its active role on the board make that the representation of civil society is not exhausted in the action of formal members of CEDCA.